TUHAN, IZINKAN AKU BERNYANYI: ROCKER MUSLIMAH SUNDA DAN RESISTENSI TERHADAP STEREOTYPE - Noorbani, Muhammad Agus; Nur, Mahmudah (Jurnal Studi Gender dan Anak, 2022)
This paper provides an analysis of resistance carried out by a rock band called Voice of Baceprot (VoB). VoB is a group of heavy metal musicians consisting of three young Sundanese Muslimah from Garut, Indonesia. Sundanese women are usually portrayed as having ambiguous characteristics, especially as depicted in the media. Physically, they are often perceived as attractive and ageless, while their personality traits are considered hard-working, assertive, principled, smart, and trustworthy. These perceptions thus create a negative stereotype of Sundanese women, especially since it is still taboo for muslim women to do rock music. This article aims to explain how these young Sundanese muslimah resist and negotiate their freedom as expressed through heavy metal music. Content analysis is used to analyze the data, such as the interview and the lyrics of their songs. The result shows that the values of religion still prevent women, especially young women, to pursue a career in arts. How VoB fight for freedom is not driven in a frontal and disruptive way, but they use their own vulnerability as their resistance. Through the lyrics, the way they dress, and how they express themself in the media, these young women show that freedom will never oppose from being shari’a muslim.